PENGARUH PEMBERIAN KESEJAHTERAAN DAN MUTASI TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KEPEMUDAAN DAN OLAHRAGA KABUPATEN BOALEMO - Rahmi, Nur; Samiu, La Diu (Yayasan Education and Social Center, 2023)
The study was done to analyze the effect of the well-being and mutations to employee of the Youth Education and Sports Service of Boalemo District.The method of research used is a survey method with a quantitative approach.A sample of 50 responders determined by using saturated samples.Research variables are a gift of well-being ( X1 ), mutation ( x2 ) and work spirit (Y ).Data analyzed used Path Analysis. Result shown that a well - being variable (X1 ) and mutation ( X2 ) affect the simultaneous working spirit of employees. F test at 95th trust level % statistically has a significant effect on employee labor (Y) with the value of sig propability = 0.05. T-test result shown partially well-being variables ( X1 ) affect the size of 0.705 or 70.5 %, While mutation variables (X2) amount of 0.286 or 28.6%